An evaluation framework for juvenile defense: A theory of change and logic model measurements. (30th December 2022) - Pelletier, Emily K.
Abstract: This paper presents an evaluation framework for juvenile defense. The evaluation framework establishes a theory of change, logic model categories, and potential measurements for understanding the systemic variation in juvenile defense across the US. Grounded in the US Supreme Court case affirming the due process right to defense counsel, In re Gault, the evaluation framework offers a method of studying juvenile defense to assist youth in delinquency court, defenders, policymakers, and researchers. The methodological shift to an evaluation framework asserts a refocus on the legal objectives for provision of defense counsel in delinquency court.